Cancer Stem Cells and Nanomedicine - Entela Shkembi; Nicola Daniele; Francesco Zinno; Gallo Emiliano Omar (Annals of Cytology and Pathology - Peertechz Publications, 2016)
physiological process of cell renewal necessary for the survival of the organism. For tissues such as blood and skin is a daily replacement with younger cells that replace the old ones. In other tissues, such as brain and heart, this replacement is much more reduced. At the base of these regenerative processes there are populations of reserve cells located in different tissues, the more abundant the greater the regenerative capacity and the necessity of that tissue. Immature cells capable of self-maintained, that is, endlessly multiplied by generating identical cells to themselves. While replicating, stem cells also retain the ability to specialize in different mature cell types of the tissues and organs in which they are located. It is through for the double activity that stem cells of our body replicate and specialize every day to replace worn cells and allow the body to survive. It was the Russian scientist Alexander Maximov in 1906 to introduce for the first time the term 'stammzelle' (from "Stamm", jamb, and "zelle", cell) to refer to individual cells of a cell lineage progenitors. And it is of the fifties the first experimental evidence of the existence of stem in the body. However, the searchlights have been turned on these cells only since 1998, when a special stem cell has been isolated from human blastocyst (an early stage of embryo development): the embryonic stem cell.